Pediatric solitary pulmonary tuberculoma mimicking peripheral pulmonary hamartoma with extensive pleural adhesions: a case report - Mao, Kaiyi; Shang, Xianhui; Wang, Leibo; Wang, Cao; Mao, Yuchen; Zhou, Guangxu; Zhao, Peng; Tan, Hongyang; Luo, Zhen; Ma, Hong (Frontiers in Medicine, 2025)
This report describes a rare case of solitary pulmonary tuberculoma in a pediatric patient. A 13-year-old male presented with a progressively enlarging solitary nodule in the left lung, identified via chest computed tomography (CT). The patient had no obvious symptoms of tuberculosis and no known history of exposure. The tuberculin skin test was negative. The imaging findings strongly resembled a peripheral pulmonary hamartoma, leading to a preliminary diagnosis of pulmonary hamartoma with plans for video-assisted thoracoscopic surgery resection. Intraoperative findings revealed extensive and dense pleural adhesions, complicating both the identification of the lesion and surgical procedures. Postoperative pathology confirmed pulmonary tuberculoma. Additional diagnostic tests, including acid-fast bacillus staining, Mycobacterium tuberculosis polymerase chain reaction, and T-cell immunospot test for tuberculosis infection, all returned positive results. The patient recovered without complications and received standard anti-tuberculosis therapy. No recurrence was observed during a 12-month follow-up. Therefore, in cases of solitary pulmonary nodules in children, particularly in regions with high tuberculosis prevalence, pulmonary tuberculoma should be considered, even when imaging features are consistent with pulmonary hamartoma. It is recommended that tuberculosis screening be enhanced through a combination of interferon-gamma release assay and tuberculin skin test, with needle biopsy employed when necessary to improve diagnostic accuracy and prevent misdiagnosis. Additionally, for pediatric patients with pulmonary tuberculoma, the potential impact of tuberculous pleuritis should be considered preoperatively, and anti-tuberculosis therapy may be required before surgery to reduce operative risks.